Value Chain Development for Jobs in Lagging Regions - Let's Work Program in Tunisia Overview of the Approach, Impact, and Findings - Weber, Michael (The World Bank, 2020)
This report provides an overview of a World Bank activity to support structural change for competitiveness and employment opportunities in Tunisia's lagging regions based on value chain and cluster analysis. While state-level policy changes are necessary and important contributions to tackle low growth and job creation in a country, they are often not sufficient. To be effective, these policies need to be accompanied with interventions that address both market and government failures at the local level. The ultimate objective is to create more and better jobs in small and medium-size enterprises by strengthening their competitiveness in a diversified range of markets. The overview report provides the main findings of the value chain and jobs survey, the two related market analyses, and the local capacity building effort that supported the creation of the "Taskforce for Value Chain and Cluster Development" in Tunisia. Each aspect is also covered in a dedicated companion report